Passivated Perovskite Crystallization via g‐C3N4 for High‐Performance Solar Cells - Jiang, Lu‐Lu; Wang, Zhao‐Kui; Li, Meng; Zhang, Cong‐Cong; Ye, Qing‐Qing; Hu, Ke‐Hao; Lu, Ding‐Ze; Fang, Peng‐Fei; Liao, Liang‐Sheng (Advanced functional materials, 2018)
Organometallic halide perovskite films with good surface morphology and large grain size are desirable for obtaining high‐performance photovoltaic devices. However, defects and related trap sites are generated inevitably at grain boundaries and on surfaces of solution‐processed polycrystalline perovskite films. Seeking facial and efficient methods to passivate the perovskite film for minimizing defect density is necessary for further improving the photovoltaic performance. Here, a convenient strategy is developed to improve perovskite crystallization by incorporating a 2D polymeric material of graphitic carbon nitride (g‐C3N4) into the perovskite layer. The addition of g‐C3N4 results in improved crystalline quality of perovskite film with large grain size by retarding the crystallization rate, and reduced intrinsic defect density by passivating charge recombination centers around the grain boundaries. In addition, g‐C3N4 doping increases the film conductivity of perovskite layer, which is beneficial for charge transport in perovskite light‐absorption layer. Consequently, a champion device with a maximum power conversion efficiency of 19.49% is approached owing to a remarkable improvement in fill factor from 0.65 to 0.74. This finding demonstrates a simple method to passivate the perovskite film by controlling the crystallization and reducing the defect density. Graphitic carbon nitride (g‐C3N4) is incorporated into the perovskite precursor solution to modify the perovskite film by controlling the perovskite crystallization, reducing the intrinsic defect density, and improving the film conductivity. As a result, a champion device with a maximum power conversion efficiency of 19.49% is approached.